Response to growth hormone according to provocation test results in idiopathic short stature and idiopathic growth hormone deficiency - Ju Young Yoon; Chong Kun Cheon; Jung Hyun Lee; Min Jung Kwak; Hyun-Ji Kim; Ye Jin Kim; Jeong Eun Lee; Woo Yeong Chung; Jeongyun Kim; Jae-Ho Yoo (Korean Society of Pediatric Endocrinology, 2022)
Purpose To investigate growth response in children with either idiopathic short stature (ISS) or growth hormone (GH) deficiency (GHD). Methods The data of prepubertal GHD or ISS children treated using recombinant human GH were obtained from the LG Growth Study database. GHD children were further divided into partial and complete GHD groups. Growth response and factors predicting growth response after 1 and 2 years of GH treatment were investigated. Results This study included 692 children (98 with ISS, 443 partial GHD, and 151 complete GHD). After 1 year, changes in height standard deviation score (ΔHt-SDS) were 0.78, 0.83, and 0.96 in ISS, partial GHD, and complete GHD, respectively. Height velocity (HV) was 8.72, 9.04, and 9.52 cm/yr in ISS, partial GHD, and complete GHD, respectively. ΔHt-SDS and HV did not differ among the 3 groups. Higher initial body mass index standard deviation score (BMI-SDS) and midparental height standard deviation score (MPH-SDS) were predictors for better growth response after 1 year in ISS and the partial GHD group, respectively. In the complete GHD group, higher Ht-SDS and BMI-SDS predicted better growth response after 1 year. After 2 years of GH treatment, higher BMI-SDS and MPH-SDS predicted a better growth outcome in the partial GHD group, and higher MPH-SDS was a predictor of good growth response in complete GHD. Conclusions Clinical characteristics and growth response did not differ among groups. Predictors of growth response differed among the 3 groups, and even in the same group, a higher GH dose would be required when poor response is predicted.